(untitled) (Conferencea, 2022)
The article analyzes the superphosphate mineral fertilizer manufacturing process, problems, and equipment designs used. Based on the analysis, an improved construction scheme of a two-part nozzle for a drum dryer is recommended. Systematic analysis of the proposed nozzle with similar structures was carried out and its effect on the heat exchange process in the drum dryer was studied. The MATLAB program was used in the multi-stage analysis and parameters calculation in the working zone of the drum dryer.